Improving Water, Sanitation, and Hygiene (WASH), with a Focus on Hand Hygiene, Globally for Community Mitigation of COVID-19 - Medley, Alexandra; Osborne, Taylor; Kesande, Maureen; Tusabe, Fred; Mwaki, Alex (PLOS Water, 2022)
Continuity of key water, sanitation, and hygiene (WASH) infrastructure and WASH practices—for example, hand hygiene—are among several critical community preventive and mitigation measures to reduce transmission of infectious diseases, including COVID-19 and other respiratory diseases. WASH guidance for COVID-19 prevention may combine existing WASH standards and new COVID-19 guidance. Many existing WASH tools can also be modified for targeted WASH assessments during the COVID-19 pandemic. We partnered with local organizations to develop and deploy tools to assess WASH conditions and practices and subsequently implement, monitor, and evaluate WASH interventions to mitigate COVID-19 in low- and middle-income countries in Latin America and the Caribbean and Africa, focusing on healthcare, community institution, and household settings and hand hygiene specifically. Employing mixed-methods assessments, we observed gaps in access to hand hygiene materials specifically despite most of those settings having access to improved, often onsite, water supplies. Across countries, adherence to hand hygiene among healthcare providers was about twice as high after patient contact compared to before patient contact. Poor or non-existent management of handwashing stations and alcohol-based hand rub (ABHR) was common, especially in community institutions. Markets and points of entry (internal or external border crossings) represent congregation spaces, critical for COVID-19 mitigation, where globally-recognized WASH standards are needed. Development, evaluation, deployment, and refinement of new and existing standards can help ensure WASH aspects of community mitigation efforts that remain accessible and functional to enable inclusive preventive behaviors.